Isothermal oxidation study on NiMnGa ferromagnetic shape memory alloy at 600-1000°C - Kok, Mediha; Pirge, Gursev; Aydogdu, Yildirim (Elsevier, 2013)
Oxidation behavior of NiMnGa alloy has been investigated under isothermal temperature by thermo gravimetric analysis (TGA), X-ray diffraction (XRD) and scanning electron microscopy equipped with an energy dispersive X-ray (SEM-EDX) spectroscope systems. The Ni-28.5Mn-20.5Ga alloy (composition in atomic percent) was exposed to oxygen atmosphere isothermally, i.e., between 600 degrees C and 1000 degrees C, for 1 h. A gravimetric method was used to determine the oxidation kinetics; weight gain per unit area as a function of time. It was determined that the oxidation constant increases significantly with isothermal temperature. Activation energy of the oxidation was found to be 152 kJ/mol. X-ray diffraction patterns of the heat-treated samples contain oxide peaks, mainly belonging to Mn3O4. X-ray analyses demonstrate that the amount of the oxide increases with isothermal temperature while that of martensite phase decreases. The scanning electron microscopy equipped with an energy dispersive X-ray (SEM-EDX) spectroscope analysis also gives the same result. According to magnetic measurements, the saturation of NiMnGa alloys decreases with rising isothermal oxidation temperature. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Oxidation; Isothermal; NiMnGa; Mass gain; Activation energy